Rhizomatous geophytes from the genus Hosta in Western Siberia - Sedelnikova Lyudmila (EDP Sciences, 2021)
This is research of biological features of the growth and development rhythm of 11 Hosta species in the conditions of forest-steppe zone of Western Siberia. A comparative analysis of the organogenesis of the species H. decorata, H. sieboldiana, and H. lancifolia is carried out. The seed productivity and viability of pollen of 9 species were established. It is provided the description of upper and lower epidermis, cross section of leaf. It is revealed that the structure of lamina is characterized by xeromesophytic characters. It is mentioned species specificity in arrangement of adaxial and abaxial stomas pursuant thereto leaves of two types of Hosta are amphistomatic and hypostomatic. It is concluded that on the lower epidermis of the leaf, the transpiration capacity is 3 – 8 times greater.